Coronal tissue loss in endodontically treated teeth (2012)
Aim: To categorize the endodontically treated teeth according to the extent of coronal tissue loss in order to determine the appropriate restoration required. Material and methods: A two year descriptive study was done at the Conservative Clinic of the Department of Restorative Dentistry, Dental Centre, University College Hospital, Ibadan. Successful endodontically treated teeth were assessed and categorized according to the extent of tissue loss based on standard criteria proposed by Smith and Schuman. Results: Two hundred and ninety endodontically treated teeth were assessed for success both clinically and radiographically. Eighty (27.6%) were anterior teeth, 78 (26.9%) were premolars while 132 (45.5%) were molars. Dental caries was found to be the most common (61.4%) indication for endodontic treatment and caused more coronal tissue damage (moderate and significant) when compared with other indications for endodontic treatment. Two hundred and twenty seven (78.3%) endodontically treated teeth had moderate coronal tissue loss, 41 (14.1%) had minimal damage while 22 (7.6%) had significant tissue damage. Dental caries was the most common indication for endodontic treatment of the posterior teeth while trauma was the most common indication for the anterior teeth. Conclusion: Majority of the endodontically treated teeth that were evaluated for tissue loss had moderate coronal tissue damage. It is therefore recommended that proper and prompt evaluation of the remaining coronal tooth tissue following successful endodontic treatment be carried out in order to determine the appropriate definitive restoration required that will be easy for the clinician and less